PARENTING FOR CHILDREN BORN OUT OF WEDLOCK - Mawaddah Nasution (Proceeding International Seminar of Islamic Studies, 2022)
: Like a valid marriage, that is harmoniously and religiously fulfilled, has a groom and a bride, is married by a guardian, is attended by witnesses, has an ijab qabul, and does not violate religious rules or violate existing norms in society. A legal marriage will produce legal offspring in the eyes of religious and state law, but on the other side many offspring are produced from parents who violate religious rules or violate norms that apply in society, such as pregnancies that occur outside of marriage. This phenomenon occurs a lot in society, because the unpreparedness of having children at a young age has many household impacts, one of which is a lack of understanding in terms of child care. For this reason, this study aims to see an overview of the parenting patterns of young parents who were forced to marry because they were pregnant first. This study uses a qualitative approach data collection is done by observation, interviews and documentation. The result is that parenting applied by parents to children is inconsistent (more permissive) and tends to ignore because of their busyness, and their unpreparedness as parents.Keywords: Parenting, Birth Outside of Marriage